Growth and Specialized Growth Charts of Children with Congenital Hypothyroidism Detected by Neonatal Screening in Isfahan, Iran. (7th February 2013) - Feizi, Awat; Hashemipour, Mahin; Hovsepian, Silva; Amirkhani, Zeynab; Kelishadi, Roya; Yazdi, Maryam; Heydari, Kamal; Sajadi, Ali; Amini, Masoud
Abstract : Objectives. The aim of the current study was to investigate the growth status of CH, generate specialized growth charts of CH infants, and compare them with their counterparts of regional normal infants. Methods. In this prospective cohort study, 760 (345 girls and 415 boys) neonates born in 2002–2009 diagnosed by neonatal CH screening program in Isfahan were followed up from the time of diagnosis. 552 healthy children were recruited as a control group. The empirical 3rd, 15th, 50th, 85th, and 97th percentiles for height, weight, and head circumference of both sexes were determined and compared with their counterpart values of the control group. The relative frequency of patients with impaired growth for each studied variable was determined. Also, specialized growth charts of CH patients were generated. Results. The percentiles of weight, height, and head circumference of studied patients are significantly different from regional healthy children (P < 0.001 ). The relative frequency of impaired head circumference was decreased to less than 3% at the 3rd year of age and for height it reached gradually 3% and 9% at the 5th year of age for boys and girls, respectively (P < 0.05 ); however for weight still it was statistically more than 3% in both sexes. Conclusion. CH patients had impaired growth development which was improved during follow up, but the catch-up time was earlier for head circumference and later for weight.